2020
DOI: 10.1016/j.ijid.2019.11.027
|View full text |Cite
|
Sign up to set email alerts
|

HepCare Europe—A service innovation project. HepCheck: Characteristics of the patient population with active infection as defined by HCV RNA

Abstract: Background: Hepatitis C virus (HCV) is a main cause of chronic liver disease worldwide and is consistently under-diagnosed. Community-based screening initiatives, such as HepCheck, have been identified as important components of HCV care. HepCheck focuses on screening and identifying HCV RNA-positive cases in high-risk populations and linking them to care as part of a larger European project to improve HCV care (HepCare). Methods: HCV testing with a self-administered questionnaire was offered to 2822 individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Type 2 DM and CKD have a considerable impact on follow-up medical care, labor, and economy and are associated with poor prognosis and management challenges; hence, disease prevention, screening, and clinical management strategies are urgently required. 12,13 Our results showed that the average levels of glucose, eAG(GA), and eAG(HbA1c) were significantly higher in the VH group than in the control group, indicating that VH is closely associated with the occurrence of type 2 DM.…”
Section: Discussionmentioning
confidence: 63%
“…Type 2 DM and CKD have a considerable impact on follow-up medical care, labor, and economy and are associated with poor prognosis and management challenges; hence, disease prevention, screening, and clinical management strategies are urgently required. 12,13 Our results showed that the average levels of glucose, eAG(GA), and eAG(HbA1c) were significantly higher in the VH group than in the control group, indicating that VH is closely associated with the occurrence of type 2 DM.…”
Section: Discussionmentioning
confidence: 63%
“…Previous estimations of HCV prevalence in homeless PWID across Europe are commonly based on HVC antibodies and range from 35% to 70% [ 21 ]. One cohort study conducted in Europe among homeless individuals, prisoners, and PWID showed a HCV RNA prevalence ranging from 9% to 43% [ 22 ]. The proportion of HCV RNA positivity among PWID in our study is 18%, which is somewhat lower compared to that of PWID in the European Union region, which ranges between 26% and 90% (Studies 8, 16–19 in: [ 23 ]).…”
Section: Discussionmentioning
confidence: 99%
“…HepCare Europe is a project co-funded by the European Commission whose aim was to create and implement a model of HCV management (screening, linkage to care and treatment) for patients from key populations, through outreach to the community and integrated primary and secondary care services. It is a consortium between 5 institutions from 4 countries (Ireland, United Kingdom, Spain and Romania) (6).…”
Section: Introductionmentioning
confidence: 99%